Improvement of the Catalytic Ability of a Thermostable and Acidophilic β-Mannanase Using a Consensus Sequence Design Strategy - Liang, Qingping; Zhan, Yuming; Yuan, Mingxue; Cao, Linyuan; Zhu, Changliang; Mou, Haijin; Liu, Zhemin (Frontiers in Microbiology, 2021)
In order to improve the catalytic efficiency of a thermostable and acidophilic β-mannanase (ManAK; derived from marine Aspergillus kawachii IFO 4308), three mutants were designed by amino acid sequence consensus analysis with a second β-mannanase (ManCbs) which also belongs to the glycoside hydrolase family 5 (GH5) and has excellent catalytic efficiency. Three mutants were constructed and their biochemical characteristics were measured after heterologous expression in Pichia pastoris. The results revealed that the kcat/Km values of the three recombinant mannanases ManAKC292V, ManAKL293V, and ManAKL294H were enhanced by 303.0%, 280.4%, and 210.1%, respectively. Furthermore, ManAKL293V showed greater thermostability than ManAK, retaining 36.5% of the initial enzyme activity after incubation at 80 °C for 5 min. This study therefore provides a rational design strategy based on consensus sequence analysis to develop industrially valuable β-mannanase for future applications in marine aquafeed.